Complete genome sequence of Pseudomonas aeruginosa YK01, a sequence type 16 isolated from a patient with keratitis - Shuo Jiang; Mengmin Ye; Ke Liu; Huiluo Cao; Xiaoshan Lin (BMC Genomic Data)
Abstract Objectives Pseudomonas aeruginosa, a Gram-negative opportunistic pathogen, is frequently associated with multidrug resistance and global epidemic outbreaks, contributing significantly to morbidity and mortality in hospitalized patients. However, P. aeruginosa belonging to the sequence type (ST) 16 was rarely reported. Here, this report presents the complete genome sequence of YK01, a ST16 P. aeruginosa isolate from a patient with keratitis. The complete reference genome of P. aeruginosa YK01 is expected to provide valuable data for investigating its genomic population, enhancing understanding of genetic basis of P. aeruginosa species complex. Data description A complete genome of 6.3 Mb was obtained for P. aeruginosa YK01 by combining Illumina 150-bp short reads and Nanopore long reads. The assembly is fully complete with chromosomal genome size of 6,183,266 bp, presenting a GC content of 66.7%, and a plasmid with the size of 46,067 bp, presenting GC content of 59.0%. Predicted chromosomal genomic features include 5,709 CDS, 12 rRNAs, 63 tRNAs, 4 ncRNAs, and 5,788 genes. To our knowledge, this genome data represents the first complete genome of P. aeruginosa ST16, providing crucial information for further comparative genome analysis.